PENGARUH CITRA MEREK TERHADAP MINAT BELI PADA MAKANAN FAST FOOD AYAM GORENG (STUDI PADA KONSUMEN TEXAS CHICKEN PEKANBARU) - Randi "; Meyzi Heryanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The problems in this research are the decline in sales and unachievement of sales target that have been set. The purpose of this research are to investigate and analyze brand image, and buy interest to know the influence of brand imgae to buy interest of texas chiken. The results of this research concluded that buy interest in texas chicken found a deal, which mean the responden agree with brand image of texas chicken at this time that. Give product innovation, presenting accurate in product information, competitive price and has a good looking product. Buy interest of texas chicken Pekanbaru rated interest. Analysis using SPSS showed that the brand image has a very strong relation with texas chicken buy interst. Brand image has positive effect to buy interest, so if there is an increase to the brand image of texas chicken it will increase the texas chicken buy interst as well.Keyword : Brand Image, Buy Interest